Evaluation of Micro- and Nano-Bismuth(III) Oxide Coated Fabric for Environmentally Friendly X-Ray Shielding Materials - Supranee Kaewpirom; Khaisang Chousangsuntorn; Siridech Boonsang (My University, 2022)
This research focuses on the development of environmentally friendly textile-based shielding composites, from micro-sized and nanosized Bi2O3 particles, against ionizing radiation. Polyester fabric dyne-coated with either micro- or nano-Bi2O3 particles shields some X-rays but the effectiveness is poor. With only ∼58% uptake of micro-sized Bi2O3 particles dyeing on polyester fabric, the insufficient amount of Bi2O3 leaded to the low density of particles, resulting in only 30% of X-ray shielding at 80 kVp. Cotton fabric coated with either micro- or nano-Bi2O3/poly(vinyl alcohol) (PVA) composites, on the other hand, demonstrated the capacity to attenuate X-ray generated by high diagnostic X-ray tube voltages of 70–100 kVp, in compliance with medical protection requirements. The X-ray attenuation performance of cotton fabric coated with either micro-Bi2O3/PVA or nano-Bi2O3/PVA nanocomposite decreased progressively with increasing tube acceleration voltages, however their ionizing radiation-shielding performance enhanced with the number of fabric layers. Interestingly, for all X-ray tube voltages evaluated, the micro-Bi2O3/PVA composite outperformed the nano- Bi2O3/PVA composite in terms of X-ray shielding. At a weight ratio of 66.7% Bi2O3, 10 layers of cotton fabric coated with micro- Bi2O3/PVA composite can attenuate 90, 85, and 80% of X-ray photons at 70, 80, and 100 kVp, respectively. As a result, these less harmful X-ray shielding materials have the potential to replace lead-based composites, which are highly toxic to human health and have negative environmental consequences.
Keywords: Environmentally Friendly; Bismuth; Radiation Shielding Materials Analysis